Ohrazení a brány židovských hřbitovů - Nešpor, Zdeněk R. (Lidé města, 2026)
Based on field research conducted between 2023 and 2025, the author documents the boundary walls and entrance gates of all 326 preserved Jewish cemeteries in the Czech Republic. The dominant type of enclosure consists of stone (and later stone-brick and brick) walls. Many of these were damaged during World War II and under the communist regime but have been repaired or newly rebuilt since the 1990s. Other types of fencing are marginal, typically modern, and often only temporary. Notably, one-tenth of Jewish cemeteries in the Czech Republic lack fencing entirely, despite this contradicting the requirements of Halakhah. Originally, cemetery walls were accessed via simple gates; however, from the 19th century onward, these were often replaced by ceremonial halls or mortuaries that served as throughpassages for funeral processions. While these structures have a lower rate of preservation, there has been a systematic effort since the 1990s to repair them or construct new, symbolically significant entrance gates. The author supports this quantitative analysis of the current state and evolution of these enclosures with illustrative photographs.